Stéréotypes sexués et abandon sportif?: une étude basée sur des mesures explicites et implicites - Plaza, M.; Boiché, J. (Movement & Sport Sciences - Science & Motricité, 2017)
Sex stereotypes are presumed to impact individuals' sport behaviors: (1) indirectly through the internalization of these beliefs and/or; (2) directly. Only a handful of studies focused on the association between sex stereotypes and sport disengagement, and none studied their direct link with this phenomenon. The aim of this study was to examine the relationship between explicit and implicit sex stereotypes and sport dropout in a sample of young adults (N = 83). The participants who had ceased their sport practice reported significantly higher levels of explicit pro-masculine stereotypes than did those who were still practicing. However, no effect appeared regarding implicit scores. The perspectives attached to this dual approach of social cognitions are discussed.